2007
DOI: 10.1021/cm062735u
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Olefin-Terminated Homogeneous and Mixed Monolayers on Scribed Silicon

Abstract: We describe the preparation of homogeneous olefin-terminated monolayers on scribed silicon made from 1,9-decadiene, and mixed monolayers with varying degrees of olefin termination prepared from 1,9-decadiene and 1-decene or 1-octene, and their subsequent reactions with bromine, osmium tetroxide, dicholorocarbene, and Grubbs' catalyst. Each of these reagents contains a heteroatom, which allows straightforward monitoring of the surface reactions by X-ray photoelectron spectroscopy (XPS). Surface reactions of mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…c 2007, American Chemical Society studies supported the assumptions made based on the experimental investigation [450]. Finally, the most recent work on scribed silicon surface modification using 1,9-decadiene suggested that the majority of reactions of this compound proceeds via addition of only one alkene group leaving the other to be available for further modification, as was supported by chemical verification with bromine, osmium tetroxide, dichlorocarbene, and ((cyclohexyl) 3 P) 2 Cl 2 Ru=CHPh (Grubbs' catalyst) [452].…”
Section: Chemistry Of Scribed Siliconsupporting
confidence: 54%
“…c 2007, American Chemical Society studies supported the assumptions made based on the experimental investigation [450]. Finally, the most recent work on scribed silicon surface modification using 1,9-decadiene suggested that the majority of reactions of this compound proceeds via addition of only one alkene group leaving the other to be available for further modification, as was supported by chemical verification with bromine, osmium tetroxide, dichlorocarbene, and ((cyclohexyl) 3 P) 2 Cl 2 Ru=CHPh (Grubbs' catalyst) [452].…”
Section: Chemistry Of Scribed Siliconsupporting
confidence: 54%
“…Clearly, many researchers recognize the importance of employing multiple analytical techniques to characterize surfaces and materials . However, to better understand the degree to which this message is being put into practice, we selected 13 papers from nine research groups on the topic of surface modification of hydrogen‐terminated, porous, and scribed silicon with carbon–carbon double bond containing reagents . This is an area in which one of us (MRL) has published .…”
Section: Introductionmentioning
confidence: 99%
“…For more information about these chemometrics techniques, the reader is referred to any of a number of books or papers on these topics.…”
Section: Introductionmentioning
confidence: 99%